Epstein-Barr virus, human papillomavirus and herpes simplex virus 2 co-presence severely dysregulates miRNA expression - Jude O. Okoye; Anthony A. Ngokere; Charles C. Onyenekwe; Olaposi Omotuyi; Deborah I. Dada (AOSIS, 2021)
This cross-sectional study evaluated the expression of miR-let-7b, miR-21, miR-125b, miR-143, miR-145, miR-155, miR-182, miR-200c, p53 gene, Ki67, SCCA1 and CD4+ T-cell counts among 319 women, to Epstein-Barr virus, human papillomavirus and herpes simplex virus 2 mono-infections and co-infections, using enzyme-linked immunosorbent assay and reverse transcriptase-polymerase chain reaction methods. This study suggests that malignancies associated with viral co-infection could be diagnosed early by monitoring cluster of differentiation 4+ T-cell counts and serum expression of miR-145 and miR-182.